DESIGN AND DEVELOPMENT OF AN LADM-BASED EXTERNAL DATA MODEL FOR LAND REGISTRY AND CADASTRE TRANSACTIONS IN TURKEY: A CASE STUDY OF TREASURY REAL PROPERTIES - Alkan, Mehmet; Arslan, Elif Tas (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2021)
The processes starting with the identification and registration of treasury properties have an essential place in the cadastral systems. Spatial data modelling studies were conducted in 2002 to establish a common standard structure on the fundamental similarities of land management systems. These studies were stated as a beginning named Core Cadastral Domain Model (CCDM), since 2006, it has been started to be made under the name of LADM. This model was accepted in 2012 as a standard model in the field of land administration by the International Organization for Standardization (ISO). In this study, an external model class is proposed for LADM's transactions related to Treasury's real estates properties which are related National Property Automation Project (MEOP). In order to determine the deficiency of this current external model, databases containing records related to spatial data and property rights were examined, and the deficiencies related to transactions on treasury properties were determined. The created external class is associated with the LADM's LA_Party, LA_RRR, LA_SpatialUnit and LA_BAUnit master classes. Herewith the standardization of the external data model is ensured. If the external model is implemented by the responsible standardization of the archiving processes will be more comfortable and faster to register.
Keywords: Land Administration Domain Model (LADM); Unified Modelling Language (UML); external data model; object oriented-modelling; Directorate General of National Property; Geochemistry & Geophysics; Remote Sensing